2013
DOI: 10.1080/15287394.2013.853634
|View full text |Cite
|
Sign up to set email alerts
|

Lung Alterations Following Single or Multiple Low-Dose Carbon Black Nanoparticle Aspirations in Mice

Abstract: Carbon black nanoparticle (CBNP) applications in high doses have been shown to be harmful to the lung. It is postulated that even small, environmentally relevant concentrations induce changes on lung homeostasis. The present study determined the impact of low-dose single and multiple CBNP (Printex 90) applications on mouse alveolar cell metabolism, especially inflammatory and oxidative stress parameters. Nanoparticles were administered to mice by a single or 8 oropharyngeal aspirations at wk 1, 2, 3, 5, 7, 9, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 53 publications
0
4
0
1
Order By: Relevance
“…Since AS-PAH has a similar surface area, shape, size and solubility compared to PAH-coated P90, the different effects of these particles observed in the biological systems are likely the result of its different PAH composition [61, 62]. The AS-PAH that we synthesized contained a mixture of at least 17 PAH with 2–7 aromatic rings that could be removed from the particle with organic solvents, indicating that these PAH are on the surface of the particle.…”
Section: Discussionmentioning
confidence: 99%
“…Since AS-PAH has a similar surface area, shape, size and solubility compared to PAH-coated P90, the different effects of these particles observed in the biological systems are likely the result of its different PAH composition [61, 62]. The AS-PAH that we synthesized contained a mixture of at least 17 PAH with 2–7 aromatic rings that could be removed from the particle with organic solvents, indicating that these PAH are on the surface of the particle.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple animal studies confirmed the inflammatory properties of DQ12. 45 Indeed, DQ12-exposed animals have been observed to express severe inflammatory effects following either 14d or 90d of exposure, respectively. 46,47 Therefore, the ability of DQ12 to trigger (pro-)inflammatory reactions at both the gene and protein level highlights the effectiveness of the employed in vitro chronic strategy.…”
Section: Resultsmentioning
confidence: 99%
“…CBNPs can damage different organ systems by different exposure routes, and pulmonary inhalation is known as a major route of CBNPs exposure as CBNPs can impair the respiratory system leading to lung inflammation and fibrosis [ 7 9 ]. Exposure to CBNPs is known to induce lung inflammation in vivo [ 10 , 11 ], and possesses the potential to generate reactive oxygen species (ROS) and inflammatory factors [ 12 16 ]. It has been suggested that CBNPs induce apoptosis by a ROS-dependent mitochondrial pathway in bronchial epithelial cells [ 13 ], and induce inflammatory response through ROS-NFκB pathway in macrophages [ 14 ].…”
Section: Introductionmentioning
confidence: 99%